Pengembangan Pengembangan Bahan Ajar Interaktif untuk Meningkatkan Pemahaman Konsep Matematis pada Materi Bilangan Cacah hingga 10.000 di Sekolah Dasar - Riyadi, Diki; Mufliva, Rosiana (Lembaga Yasin AlSys, 2025)
The learning of mathematics in elementary school is a mandatory subject that students must master. In mathematics, there are many topics to learn, one of which is whole numbers. Whole numbers play an essential role in students' daily lives, especially in their early understanding of numbers. This study aims to develop interactive teaching materials to enhance the mathematical concept comprehension of fourth-grade elementary school students on whole numbers up to 10,000. The research method used is Design and Development (D&D) with the ADDIE model approach (Analyze, Design, Develop, Implement, Evaluate). The results indicate that the developed teaching materials meet the criteria of being highly feasible according to subject matter experts, design experts, and teaching practitioners, with an average validation percentage exceeding 97%. The implementation of these materials among students showed a significant improvement in understanding, as reflected by an average N-Gain score of 0.96 (high category). These teaching materials were designed using digital applications with visually engaging displays, integrating interactive learning activities that are relevant to students' needs and the curriculum. This study concludes that the teaching material